2016
DOI: 10.1111/jfq.12221
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Fresh and Cooked Ground Beef can be Improved by the Incorporation of Lean Finely‐Textured Beef (LFTB)

Abstract: Ground beef was formulated into six treatments of 82 or 93% lean with 0, 10, or 20% lean finely‐textured beef (LFTB). Batches (n = 5/treatment) were ground and formed into patties, then aerobically packaged for 5 days of simulated retail display to measure fresh color and lipid oxidation (TBARS). Additional patties were cooked to 71.1C before measuring external and internal cooked color, TBARS, and Lee‐Kramer shear force (LKSF). Lightness (L*), redness (a*), and pH of fresh patties increased (P < 0.05), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…The instrumental cooked color evaluation of red to brown (630:580 nm) in ground beef patty formulations with the inclusion of plant-derived fibers was greater ( p < 0.01) for rice compared to the control suggesting that patties with the inclusion of the rice protein were redder after cooking. Previous research reported that there was no difference in internal cooked color for ground beef patties with varying lean-to-fat ratios [ 32 ]. These previous findings, along with the results from our laboratory oat protein study, suggest different lean-to-fat ratios along with varying percentages of vegetable-based proteins in the meat block could alter the internal cooked color of ground beef patties.…”
Section: Resultsmentioning
confidence: 99%
“…The instrumental cooked color evaluation of red to brown (630:580 nm) in ground beef patty formulations with the inclusion of plant-derived fibers was greater ( p < 0.01) for rice compared to the control suggesting that patties with the inclusion of the rice protein were redder after cooking. Previous research reported that there was no difference in internal cooked color for ground beef patties with varying lean-to-fat ratios [ 32 ]. These previous findings, along with the results from our laboratory oat protein study, suggest different lean-to-fat ratios along with varying percentages of vegetable-based proteins in the meat block could alter the internal cooked color of ground beef patties.…”
Section: Resultsmentioning
confidence: 99%
“…The observed increased pH could be due to the inclusion of Lean Finely Textured Beef (LFTB) in the formulation of the products for retail sale. Through processing, the pH of LFTB is often increased above that of normal fresh beef and at inclusion, has been previously shown to increase the pH of the final blended GB (Van Laack et al, 1997;Moon et al, 2016).…”
Section: Cooking Characteristicsmentioning
confidence: 97%
“…It is apparent that the variation in fat quantity could be a contributing factor for internal color fluctuations reported within the current study. The evaluation of previous research [ 44 ] along with the current results suggest that ground beef patties with different lean-to-fat ratios and the inclusion of oat protein may cause variation of the internal cooked color of the ground beef patty.…”
Section: Resultsmentioning
confidence: 53%
“…Although the differences were numerically minimal for cooked instrumental color of meat proteins containing oat protein, these results do not agree with [ 37 ], which evaluated the internal cooked color of ground beef patties with varying lean to fat ratios. The previous study [ 44 ] reported that there was not a difference in internal cooked color ( p > 0.05) in ground beef patties. It is apparent that the variation in fat quantity could be a contributing factor for internal color fluctuations reported within the current study.…”
Section: Resultsmentioning
confidence: 93%